Pembentukan Karakter Religius Melalui Pembiasaan Shalat Dhuha di MI Ma’arif Depokrejo - Hargina, Devi Yaniar Wi (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
Abstract The formation of religious character in students is very important in order to form a generation with noble morals. One of the efforts made at MI Ma'arif Depokrejo is through the practice of Duha prayers. This research aims to find out how the habit of Duha prayer plays a role in forming students' religious character. The research method used is descriptive qualitative with a causal study approach. Data collection was carried out through observation, interviews and documentation. The results of the research show that the practice of regular Dhuha prayers at school has a positive impact on the formation of students' religious character. Students become disciplined, responsible, and have a higher awareness of religious values. The practice of Duha prayer can also strengthen students' spiritual connection with God and foster good habits in daily life. Thus, the practice of Duha prayers at MI Ma'arif Depokrejo has proven to be effective in forming the religious character of students from an early age.